Crossword Puzzle Learning Media to Improve Indonesian Vocabulary Mastery for Grade 2 Elementary School Students - Sabrina Ramadhania; Hashim Adnan (Journal of Innovation and Research in Primary Education, 2022)
Vocabulary is an important aspect for students in conveying messages and opinions. However, several studies show that elementary school students' vocabulary mastery is still low. One of the efforts that can be done is to develop learning media. This study aims to develop crossword puzzle learning media in Indonesian language learning to improve vocabulary mastery of second grade students at SDN Pulogebang 11. The research method used in this study is a qualitative research method. This research was conducted at SDN Pulogebang 11 with 32 students as the subject of class II, consisting of 17 female students and 15 male students. The research data were collected using observation and documentation techniques. Based on the data obtained from the assessment results, the crossword puzzle learning media developed was feasible to be tested. The response of students to Indonesian learning material playing in my environment through the question and answer method with crossword puzzle learning media showed a good response from the second grade students of SDN Pulogebang 11.